Indicators of impaired gas exchange in patients with cardiovascular diseases through NOC - Lívia Maia Pascoal; Vanessa Emille Carvalho de Sousa; Michelle Helcias Montoril; Dayane Horta Rocha; Marcos Venícios de Oliveira Lopes; Francisca Aline Arrais Sampaio; Flávia Paula Magalhães Monteiro (Rev Rene)
The nursing diagnosis Impaired gas exchange presents strong relation with the cardiac and respiratory function, but its identification is many times accomplished without scientific evidences. A cross-sectional study aimed at comparing indicators of impaired gas exchange in patients with Acute Coronary Syndrome, Acute Myocardial Infarction and Heart Failure. The instrument contemplated health status indicators of Nursing Outcomes Classification (NOC), organized in a scale of 1 to 5. Based on such scale it was not identified the diagnosis in study, however, alterations were observed in the breathing depth and sleepiness indicators, what can indicate a possible risk status. Statistically significant differences were identified for some indicators regarding the gender and to the medical diagnoses. The results obtained contribute to a reflection about the specific necessities presented by those patients and represent a contribution for the elaboration of individualized care plans.